Reliability and validity of the self-reported Activities of Daily Living Scale for people with mental illness. Issue 2 (December 2018) - Pan, Ay-Woan; Wu, Chao-Yi; Chung, LyInn; Chen, Tsyr-Jang
Background/objectives: Patient-reported outcome measures have been found to be an effective method of reflecting client perspectives on their personal health condition. The primary aim of this study was to determine the reliability and validity of the self-reported Activities of Daily Living Scale (sf-ADLS) using Rasch analysis in Taiwan. Methods: A total of 455 people were included in this study; 224 were persons with mental illness and 231 were healthy adults. We applied Rasch analysis as the means of testing the psychometrics of the scale. Results: The final version of the sf-ADLS used in this study included 14 items, with no differential item functioning being discernible on the gender variable. The scale was found to be of use in classifying the subjects into four levels of independence. Conclusions: The revised sf-ADLS conforms to the Rasch measurement model in the formulation of a unidimensional scale. The scale can be used to measure the level of independence with acceptable reliability (internal consistency as 0.9) and validity.